Coordination of Traffic Signals on Arterial Streets in Duhok City - Dilshad Ali Mohammed; Aso Faiz Saeed Talabany (Zanco Journal of Pure and Applied Sciences, 2021)
Duhok City lies in the north of Iraq and it has mountainous terrain. The poor road infrastructure of the city and also the daily increasing number of vehicles had left no choice other than applying traffic control systems to solve congestion problems in the city streets. Traffic control signal coordination which is one of efficient method of traffic control system that can improve the traffic operation and safety for series of signalized intersections along the arterials in the city. In this study the benefit of actuating traffic signal coordination was evaluated, and comparison in control delay against the same signalized intersection in case of being isolated was made. To achieve this four successive signalized intersections on Barzani street and three successive signalized intersections on Zakho street which are two major arterials in Duhok City were chosen. Traffic data (traffic volumes, vehicle link and approach speeds, and passenger car equivalent) during peak hours were collected. Also, geometric data and signalization data were collected using different methods, such as video recording technique, moving vehicle method and manual methods. To check the coordination attainability, the coupling index and key intersection was determined, then time-space diagrams were constructed representing one-way coordination for the intersections on Barzani and Zakho Streets, and others represented two-way coordination for the intersections on Zakho Street with acceptable progression bandwidth efficiency. The results of this study showed that a progression bandwidth of 54 seconds for east direction coordination and 17 seconds for west direction coordination on Barzani Street under suggested controlled speed of 60 kph pleasant with the present data. For Zakho Street, the progression bandwidth is 19 seconds for east direction coordination and 18 seconds for west direction coordination under suggested controlled speed of 40 kph. The results show that traffic signal coordination had led to high reduction in intersection control delays. On Barzani arterial street the reduction was between 16.2% and 51.8%, while for Zakho arterial street the reduction ranges between 16.93% and 26.11%.